Peranan Wakaf dalam Pembangunan Ekonomi di Negeri Perak: The Role of Waqf in the Economic Development of Perak - Nazeri, Amelia Nur Natasha Abdul; Ab Rahman, Asmak Abdul (Jurnal Fiqh, 2021)
The role of waqf in economic development is evident in how waqf instruments enable various economic activities. In Perak, Majlis Agama Islam dan Adat Melayu Perak (MAIPk) manages the development of waqf assets by acting as sole trustee in the development of waqf property in that state. This study analyzes the role of waqf in the economic development of Perak. The primary method used to obtain data was through interviews with MAIPk about the management and development of waqf projects. Secondary data was collected through various references such as books, theses and journals. The data thus collected was analyzed using thematic analysis according to the focus of the study. The study found that waqf played a role in the economic development of Perak’s health, education, and the improvement of income and its community’s standard of living. The outstanding development in the health sector was the construction of a waqf hemodialysis center. In the educational sector, waqf funds and instruments, contributed to the construction of the Islamic University Sultan Azlan Shah Dormitory (UISAS) and Maahad Tahfiz. Waqf also contributed to improving the income and living standards of the community in Perak through various projects such as the Wakaf Business Centre (WBC) project, waqf housing, and waqf boats to develop the economy of the community in Perak.